Analysis of quenching temperature variations in the heat straightening processFor multiple ripair FCAW welding HSLA SM490YA material - Wahyudi, Mohammad Thoriq; Amri, Moh Syaiful Amri; Ari, Muhamad; Adam, Mukhlis; Hamzah, Fais; Novaldi, Azriel Harsha (Politeknik Negeri Lhokseumawe, 2023)
In the steel structure fabrication industry, girders play a crucial role as supporting beams during construction. The girder's components include end plates and beams, with the end plate serving as a critical connection point for the beam to the column. Welding at this juncture demands careful consideration. This analytical research focuses on the impact of multiple repair welding and quenching temperatures during the heat straightening process on the toughness and microstructure of HSLA SM490YA material, utilizing FCAW welding. To assess the effects of multiple repair welding, the study compares different repair scenarios—welding without repair, two repairs, and three repairs, all performed at a 50% depth. Subsequently, the heat straightening process occurs at a temperature of 650ºC on the repaired material. Post-heat straightening, quenching is carried out with temperature variations of 650ºC, 475ºC, and 300ºC. The findings indicate that the repair process during welding and subsequent quenching after the heat straightening process leads to a decrease in toughness values. This results in a finer grain size, with the material phase predominantly composed of pearlite. These research outcomes should be carefully considered by industry professionals, particularly in critical connections, when determining quenching temperatures after the heat straightening process in repair procedures.